Synaptic NMDA receptor activity at resting membrane potentials - Chiu, Delia N.; Carter, Brett C. (Frontiers in Cellular Neuroscience, 2022)
NMDA receptors (NMDARs) are crucial for glutamatergic synaptic signaling in the mammalian central nervous system. When activated by glutamate and glycine/D-serine, the NMDAR ion channel can open, but current flux is further regulated by voltage-dependent block conferred by extracellular Mg2+ ions. The unique biophysical property of ligand- and voltage-dependence positions NMDARs as synaptic coincidence detectors, controlling a major source of synaptic Ca2+ influx. We measured synaptic currents in layer 2/3 neurons after stimulation in layer 4 of somatosensory cortex and found measurable NMDAR currents at all voltages tested. This NMDAR current did not require concurrent AMPAR depolarization. In physiological ionic conditions, the NMDAR current response at negative potentials was enhanced relative to ionic conditions typically used in slice experiments. NMDAR activity was also seen in synaptic recordings from hippocampal CA1 neurons, indicating a general property of NMDAR signaling. Using a fluorescent Ca2+ indicator, we measured responses to stimulation in layer 4 at individual synaptic sites, and Ca2+ influx could be detected even with AMPARs blocked. In current clamp recordings, we found that physiological ionic concentrations shift both resting membrane potential and AP firing threshold, and that NMDARs contribute to EPSPs at resting membrane potentials. These measurements demonstrate that, even in the presence of extracellular Mg2+ and absence of postsynaptic depolarization, NMDARs contribute to synaptic currents and Ca2+ influx.